2004
DOI: 10.1074/jbc.m310264200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Inhibits Cyclin A Expression and Retinoblastoma Hyperphosphorylation Triggered by Insulin-like Growth Factor-I Induction of New E2F-1 Synthesis

Abstract: Cyclin A is required for cell cycle S phase entry, and its overexpression contributes to tumorigenesis. Release of pre-existing E2Fs from inactive complexes of E2F and hypophosphorylated retinoblastoma (RB) is the prevailing dogma for E2F transcriptional activation of target genes such as cyclin A. Here we explored the hypothesis that new synthesis of E2F-1 is required for insulin-like growth factor-I (IGF-I) to induce cyclin A accumulation and RB hyperphosphorylation, events that are targeted by tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Our results suggest that at least a portion of this effect of TNFa is due to the inhibition of IGF-I actions. Our results are also consistent with those showing that TNFa inhibited basal and IGF-I-mediated proliferation in human mammary epithelial cells (Shen et al 2004). Unlike others, however, we found that high doses of IL-6 and IL-1b (50 and 100 ng/ml respectively) did not affect basal or IGF-I-stimulated proliferation of bovine mammary cells.…”
Section: Discussionsupporting
confidence: 82%
“…Our results suggest that at least a portion of this effect of TNFa is due to the inhibition of IGF-I actions. Our results are also consistent with those showing that TNFa inhibited basal and IGF-I-mediated proliferation in human mammary epithelial cells (Shen et al 2004). Unlike others, however, we found that high doses of IL-6 and IL-1b (50 and 100 ng/ml respectively) did not affect basal or IGF-I-stimulated proliferation of bovine mammary cells.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, inhibition of E2F-1 transcription caused by treatment with atRA should lead to a profound decrease in the level of E2F-1 as observed in Figure 2b. A recent study has shown that inhibition of E2F-1 transcription by siRNA in breast cancer cells blocks Rb-phosphorylation and interference of this feed-forward loop would be an efficient barrier to neoplastic cell cycling (Shen et al, 2004). So far, we have studied two different E 2 -responsive breast cancer cell lines and our results indicate that, in both cases, HES-1 has to be downregulated for E 2 to stimulate cellular proliferation (Strom et al, 2000;Muller et al, 2002).…”
Section: Discussionmentioning
confidence: 91%
“…A recent report has shown that PBK transcription is regulated by E2F and cAMP-response element binding protein (CREB) (Nandi and Rapoport, 2006). CREB is activated by IGF-I through the PI3K and ERK pathways (Maldonado et al, 2005); whereas IGF-I can also induce E2F expression (Shen et al, 2004). It is likely that E2F and CREB could be the transcription factors responsible for IGF-I-induced PBK expression.…”
Section: Discussionmentioning
confidence: 99%